Development of Micro, Small and Medium Enterprises and Their Constraints: A Story from Indonesia - Tulus T. H. Tambunan (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2011)
The main aim of this paper is to discuss recent development of micro, small and medium enterprises (MSMEs) and their current problems in Indonesia, based on analysis of secondary data on their performance focusing on their contribution to gross domestic product (GDP) and productivity, and their constraints. It shows that their GDP share is larger than that of large enterprises (LEs). But it is mainly because their number is huge, while their productivity is low. Their main constraints are mainly high cost of raw materials, marketing difficulties, and lack of capital.